Polysaccharides : natural fibers in food and nutrition - Benkeblia, Noureddine (Boca Raton : CRC Press, 2014)
'This book reviews the evidence supporting the influence of plant fibers on our daily life by either having impacts on our nutrition or improving processed foods for human and animal feeding. By bringing new information and updating existing scientific data, this book will also be a consistent source of information for both professional and non-professionals that are involved in food science and technology, nutrition, and even medical sciences related to human health and well-being'--
'In a web search for'sugar factory,' the site that most closely resembled a factory that makes sugar was a large sugar refinery and its expansion plans in New York City. It is noteworthy that despite our remarkable technological advances, we still cannot duplicate one of the most common activities of the plant kingdom--manufacturing sugar. I do not mean extracting it from plants and purifying it (making it white); that's easy. I mean building sugar molecules with carbon atoms like plants do in photosynthesis. One could argue that there are no man-made sugar factories because it is simply not cost-effective; it would be a losing proposition to compete with plants at this business. The first time I read about photosynthesis, I thought it seemed impossible that plants could take carbon dioxide and water and, using energy from the sun, produce sugar. These little sugar factories absorb carbon dioxide from the air at a concentration of about 0.04%, amid overwhelming concentrations of nitrogen and oxygen. And, when they are finished, they'discard' oxygen as a waste product! But they don't stop there, which is what this book is all about. If they don't use the monosaccharide products of photosynthesis directly, they hook them together to form disaccharides, oligosaccharides, and polysaccharides. The types of linkages between monosaccharides make for an incredible diversity of structure and function. Cellulose, starch, fructan, and B-glucan, are some of the products of the plant and fungal species described in this book'--
Includes bibliographical references and index.
Keywords: Fiber in human nutrition; Polysaccharides; Plant fibers